Letter - Norris, Donald C.
032-0091-001 Telephone No. National 9917 (2 lines) 14, City Road, Finsbury Square, E.C.1. 1st March, 1939. The Secretary, International Solidarity Fund. Dear Sir, I enclose herewith cheque for £2 - 2 - 0 in respect or subscription to your Fund for the month of February. I should be grateful if you would be good enough to let me know the present position and future prospects of your organisation, and particularly how you propose to deal with the situation created by the Government's action in recognising General Franco. What has been the effect of the occupation of Catalonia by the insurgents? Are you still able to send relief to the Spanish Government territory in the south? I understand that the Post Office no longer accepts mail for this region. Does your Fund assist the refugees now in the south of France? Yours faithfully, Donald C. Norris. 292/946/32/91